Chloroplast Phylogenomics Reveals the Intercontinental Biogeographic History of the Liquorice Genus (Leguminosae: Glycyrrhiza) - Duan, Lei; Harris, A.J.; Su, Chun; Zhang, Zhi-Rong; Arslan, Emine; Ertuğrul, Kuddisi; Loc, Phan Ke; Hayashi, Hiroaki; Wen, Jun; Chen, Hong-Feng (Frontiers in Plant Science, 2020)
The liquorice genus, Glycyrrhiza L. (Leguminosae), is a medicinal herb with great economic importance and an intriguing intercontinental disjunct distribution in Eurasia, North Africa, the Americas, and Australia. Glycyrrhiza, along with Glycyrrhizopsis Boiss. and Meristotropis Fisch. & C.A.Mey., comprise Glycyrrhiza s.l. Here we reconstructed the phylogenetic relationships and biogeographic history in Glycyrrhiza s.l. using sequence data of whole chloroplast genomes. We found that Glycyrrhiza s.l. is sister to the tribe Wisterieae and is divided into four main clades. Clade I, corresponds to Glycyrrhizopsis and is sister to Glycyrrhiza sensu Meng. Meristotropis is embedded within Glycyrrhiza sensu Meng, and these two genera together form Clades II-IV. Based on biogeographic analyses and divergence time dating, Glycyrrhiza s.l. originated during the late Eocene and its most recent common ancestor (MRCA) was distributed in the interior of Eurasia and the circum-Mediterranean region. A vicariance event, which was possibly a response to the uplifting of the Turkish-Iranian Plateau, may have driven the divergence between Glycyrrhiza sensu Meng and Glycyrrhizopsis in the Middle Miocene. The third and fourth main uplift events of the Qinghai-Tibetan Plateau may have led to rapid evolutionary diversification within Glycyrrhiza sensu Meng. Subsequently, the MRCA of Clade II might have migrated to North America (G. lepidota) via the Bering land bridge during the early Pliocene, and reached temperate South America (G. astragalina) by long-distance dispersal (LDD). Within Clade III, the ancestor of G. acanthocarpa arrived at southern Australia through LDD after the late Pliocene, whereas all other species (the SPEY clade) migrated to the interior of Eurasia and the Mediterranean region in the early Pleistocene. The MRCA of Clade IV was restricted in the interior of Eurasia, but its descendants have become widespread in temperate regions of the Old World Northern Hemisphere during the last million years.